Tourism and poverty alleviation in Bangka Belitung Islands - Nabila Nursyadza; Herniwati Retno Handayani (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This research aims to study the tourism sector's role in poverty reduction in the Bangka Belitung Islands Province. Independent variables used in this study include the number of tourists, business units in the tourism sector, and the number of employments in the tourism sector. Data from the Central Bureau of Statistics comprised six districts and one city in the Bangka Belitung Islands from 2013-2018. Ordinary least square is used in this study. The results of this study indicate that the three independent variables in the survey simultaneously affect the dependent variable. Partially, the number of tourists and business units in the tourism sector have adverse and significant effects on poverty reduction. In contrast, the employment variable in the tourism sector partially has a positive and insignificant impact on poverty reduction in the Bangka Belitung Islands Province.